Internalisasi Pendidikan ASWAJA Sebagai Konservasi Budaya di MADIN Nurul Qodim Al-Manshuriyah Pasuruan - fauzi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
Internalization of aswaja education as a preservation or process as a maintenance and protection of Islamic teachings that have been carried out for generations as a tradition rooted in society, Islamic education as an answer to safeguard and prevent by providing aswaja education as a theological bulwark of Islam which is now starting to be undermined by assumptions which is discrediting. That the culture practiced by Muslims is heresy and is not in accordance with the Shari'a so that the existence of aswaja education in the education unit becomes the basis for providing an understanding of the traditions that have been entrenched in the surrounding community that have been promoted. passed from generation to generation. which is considered as local wisdom and justified by religion. This research was conducted in Madin Nurul Qodim al-Manshuriyah Tamansari, Wonorejo, Pasuruan using an ethnographic approach. The result of this study is how students internalize the aswaja education that is learned at madrasah diniyah into a concrete cultural understanding in society and can be a bastion of radicalism thinking that justifies and blames Islamic culture that has been carried out by the Tamansari community and its surroundings.